Representasi Fear of Missing Out Dalam Iklan (Studi Semiotika Dalam Iklan Samsung Versi Join The Flip Side) - Desti Kornelia Crista; Artyasto Jatisidi; Rocky Prasetyo Jati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The phenomenon of Fear of Missing Out has become widespread as a lifestyle related to social media and the internet, however, if it is further elaborated, this phenomenon is more related to how consumers become consumptive towards ownership of an item. The purpose of this research is to find out how advertising represents the FOMO phenomenon into digital advertising messages. This research was conducted with a descriptive qualitative method, using Roland Barthes' semiotic theory, which analyzes signs at the level of denotation, connotation, and myth. Conclusion of this study show that the depiction of the Fear of Missing Out phenomenon is shown in three main stages, namely rejection with self-control, prolonged hallucinations, to decision making to achieve feelings of comfort and security.